The impact of alkali activator dosage on the compressive strength and water absorption of steel slag concrete - Ho, Chia Min; Doh, Shu Ing; A. K. A., Mohammad Al-Btoush; Li, XiaoFeng; Siew, Choo Chin (Elsevier Ltd, 2022)
Steel Slag (SS) is an alternative for cement replacement in concrete. However, high replacement rate of SS increases the workability of concrete at the same time reduces the early strength of concrete. The aim of this study is to investigate the effect of different dosage of alkali activator in concrete with 40% SS as cement replacement on its workability, compressive strength, and water absorption. In this study, different dosage of Na2SO4 were added into SS based concrete with fixed cement replacement rate at 40%. Result shows that the workability of SS based concrete decreased with the increase of Na2SO4 dosage. The early strength increases with the addition of Na2SO4 from 1 to 3% and decreased over 3%. The 28-day and 90-day strength increase with the addition of Na2SO4 from 1 to 4% and decrease over 4%. The rate of water absorption of SS based concrete reduced significantly with the increase of Na2SO4. From the experimental result, it is observed that the addition of 4% Na2SO4 gives the highest strength of 35.12 MPa at 28-day.